(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article is an analytical translation of the scientific article “Who Were the Sogdians, and Why Do They Matter?” by Judith A. Lerner and Thomas Wide into Uzbek. The article examines the role of the Sogdian civilization on the Silk Roads, their trade activities, cultural and religious diversity, and their contribution to art and literature, as well as how they disappeared from historical memory and were rediscovered through modern research. The article also considers the significance of the Sogdian culture, which was formed on the principles of mobility, openness to intercultural contacts, and cosmopolitanism, in today’s global historical context. The article analyzes the Sogdian heritage within the framework of modern scientific approaches - mobility, hybridity, and transcultural contacts.